OlympiAD final overall survival and tolerability results: Olaparib versus chemotherapy treatment of physician's choice in patients with a germline BRCA mutation and HER2-negative metastatic breast cancer. (23rd January 2019) - Robson, M E; Tung, N; Conte, P; Im, S -A; Senkus, E; Xu, B; Masuda, N; Delaloge, S; Li, W; Armstrong, A; Wu, W; Goessl, C; et al.
Abstract: Background: In the OlympiAD study, olaparib was shown to improve progression-free survival compared with chemotherapy treatment of physician's choice (TPC) in patients with a germline BRCA1 and/or BRCA2 mutation (BRCAm) and human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer (mBC). We now report the planned final overall survival (OS) results, and describe the most common adverse events (AEs) to better understand olaparib tolerability in this population. Patients and methods: OlympiAD, a Phase III, randomized, controlled, open-label study (NCT02000622), enrolled patients with a germline BRCAm and HER2-negative mBC who had received ≤2 lines of chemotherapy for mBC. Patients were randomized to olaparib tablets (300 mg bid) or predeclared TPC (capecitabine, vinorelbine, or eribulin). OS and safety were secondary end points. Results: A total of 205 patients were randomized to olaparib and 97 to TPC. At 64% data maturity, median OS was 19.3 months with olaparib versus 17.1 months with TPC (HR 0.90, 95% CI 0.66–1.23; P = 0.513); median follow-up was 25.3 and 26.3 months, respectively. HR for OS with olaparib versus TPC in prespecified subgroups were: prior chemotherapy for mBC [no (first-line setting): 0.51, 95% CI 0.29–0.90; yes (second/third-line): 1.13, 0.79–1.64]; receptor status (triple negative: 0.93, 0.62–1.43; hormone receptor positive: 0.86, 0.55–1.36); prior platinum (yes: 0.83, 0.49–1.45; no: 0.91, 0.64–1.33). Adverse events during olaparib treatment were generally low grade and manageable by supportive treatment or dose modification. There was a low rate of treatment discontinuation (4.9%), and the risk of developing anemia did not increase with extended olaparib exposure. Conclusions: While there was no statistically significant improvement in OS with olaparib compared to TPC, there was the possibility of meaningful OS benefit among patients who had not received chemotherapy for metastatic disease. Olaparib was generally well-tolerated, with no evidence of cumulative toxicity during extended exposure. Video Abstract: